Vascular endothelial growth factor facilitates the effects of telocytes on tumor cell proliferation and migration - Li, Fujie; Tang, Xueying; Cao, Haitao; Wang, Wenya; Geng, Chengyue; Sun, Zuyao; Shen, Xiaokun; Li, Shinan (Frontiers in Cell and Developmental Biology, 2024)
BackgroundTelocytes, recently recognized as interstitial cells with a diverse range of potential functions, have attracted considerable attention for their involvement in tumorigenesis. Nevertheless, owing to certain challenges in the isolation and cultivation of telocytes, the research on telocytes has advanced rather slowly. Therefore, it is imperative to study the role and mechanisms of telocytes in tumors.MethodsWe improved the separation method and successfully isolated telocytes by exploiting the combination of cell adhesion and magnetic bead sorting. Telocytes conditioned medium was collected to culture tumor cells and explore the role and mechanisms of telocytes in tumors.ResultsMTT and colony formation assays demonstrated that telocytes promoted tumor cell proliferation. Wound healing experiments and transwell assays indicated that telocytes enhanced tumor cell migration. Real-time reverse transcriptase PCR analysis showed that the expression of E-cadherin was decreased, and that of Vimentin was notably increased. ELISA results revealed that telocytes secreted high levels of vascular endothelial growth factor (VEGF). And the promoting effects were alleviated by the VEGF inhibitor bevacizumab.ConclusionOur findings revealed that telocytes promoted tumor cell proliferation, migration, and angiogenesis through VEGF. Notably, these effects were inhibited by the addition of bevacizumab. In conclusion, our findings illuminated the role of telocytes in promoting tumor progression, and confirmed their crucial regulatory role in the growth of tumor cells.